(untitled) (Journal of Engineering, 2015)
Reduction of noise and vibration in spur gear experimentally by using asymmetric teeth profiles with tip relief was presented. Both of classical (symmetric) and asymmetric (with and without tip relief) spur gears are used in this work. Gear test rig was constructed to achieve torsional vibration measuring, and two modified cutters are designed and manufactured to achieve tooth profile modifications. First to cut asymmetric gear tooth with pressure angles (14.5o/25 o) without tip relief for loaded and unloaded tooth sides respectively, and second to cut asymmetric gear tooth with pressure angles (14.5o/25 o) for loaded and unloaded tooth sides respectively with tip relief to achieve best dynamic performance. Dynamic load factor, transmission error and noise level are carried out in this work. Final results showed improvement in dynamic load factor and noise level for asymmetric gear (with and without tip relief) compared with classical spur gear .